2022
DOI: 10.1029/2021wr030680
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Monitoring of Controlled Water Table Variations From Dense Seismic‐Noise Acquisitions

Abstract: Unconfined aquifers are an essential water resource. Their preservation in terms of both quantity and quality is a major challenge due to the expected impacts of climate change and their exploitation by human activities. Among others, managed aquifer recharge (MAR) is a practice of increasing interest which is commonly applied to stormwater management in urban areas (Machiwal et al., 2018;Zhang et al., 2020) or water reuse (Zhang et al., 2020). Using infiltration basins or trenches, MAR systems could generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Regardless of the aforementioned limitations, there remain opportunities to combine passive seismology with hydrological and geodetic studies. Direct comparisons between dv/v and groundwater wells (Clements & Denolle, 2018; Kim & Lekic, 2019; Sens‐Schönfelder & Wegler, 2006), GPS (Clements & Denolle, 2018; Tsai, 2011), InSAR (Mao et al., 2022), piezo‐electric (Gaubert‐Bastide et al., 2022) present opportunities for future monitoring of the near‐surface. In particular, there are promising possibilities of joint analysis with hydro‐geodesy work (Borsa et al., 2014; Carlson et al., 2020; Gualandi & Liu, 2021; White et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the aforementioned limitations, there remain opportunities to combine passive seismology with hydrological and geodetic studies. Direct comparisons between dv/v and groundwater wells (Clements & Denolle, 2018; Kim & Lekic, 2019; Sens‐Schönfelder & Wegler, 2006), GPS (Clements & Denolle, 2018; Tsai, 2011), InSAR (Mao et al., 2022), piezo‐electric (Gaubert‐Bastide et al., 2022) present opportunities for future monitoring of the near‐surface. In particular, there are promising possibilities of joint analysis with hydro‐geodesy work (Borsa et al., 2014; Carlson et al., 2020; Gualandi & Liu, 2021; White et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The following year, Wegler and Sens‐Schönfelder (2007) measured a sudden decrease in seismic wave speed following the 2004 M 6.6 Mid‐Niigata Earthquake. Since then, numerous studies have found the significant influence of thermoelastic stresses (Ben‐Zion & Leary, 1986; Lecocq et al., 2017; Richter et al., 2014; Snieder et al., 2002; Tsai, 2011), measured and inferred pore‐pressure changes (Andajani et al., 2020; Clements & Denolle, 2018; Feng et al., 2021; Gassenmeier et al., 2015; Gaubert‐Bastide et al., 2022; Lecocq et al., 2017; Q.‐Y. Wang et al., 2017), tidal stresses (De Fazio et al., 1973; Mao et al., 2019; Sens‐Schönfelder & Eulenfeld, 2019; Takano et al., 2017, 2019), earthquake damage near the fault (Boschelli et al., 2021; Brenguier, Campillo, et al., 2008; Froment et al., 2013; Lu & Ben‐Zion, 2022; Obermann et al., 2014; Taira et al., 2015), and ground‐motion induced damage (Bonilla & Ben‐Zion, 2021; Bonilla et al., 2019; Rubinstein, 2004; Viens et al., 2018), atmospheric loading (Gradon et al., 2021), snow loading (Donaldson et al., 2019; Q.‐Y.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an important step forward has been taken relating to the possibility of producing interpolated 2D maps of piezometric level variations (through an inversion process, e.g. [9]), a significant progress axis toward the spatial interpretation of velocity variations and a better understanding of the groundwater system's full complexity by filling the actual gap related to the local nature of piezometric measurements.…”
Section: Velocity Analysis For Groundwater Managementmentioning
confidence: 99%
“…However, in the last decade, application of seismic velocity based interferometric studies have been increasingly tested in subsurface contexts where fluids play an important role, for example relating to hydrogeologic monitoring at the shallow subsurface scale (e.g. [6,7,8,9]), or at the meso-scale [10], or for the characterization and monitoring of geothermal systems [11], among other contexts.…”
Section: Introduction -From Seismic Velocity To Seismic Attenuationmentioning
confidence: 99%